Comparative Perceptions of Fluoride Toxicity in Oral Hygiene Products: Insights from the General Population and Healthcare Professionals - Marija Badrov; Lidia Gavic; Ana Seselja Perisin; Davor Zeljezic; Jasen Vladislavic; Ema Puizina Mladinic; Antonija Tadin (Clinics and Practice)
Background: The safety of oral hygiene products is a growing concern, particularly regarding the toxicity of specific ingredients used in their formulations. The purpose of this study was to evaluate the knowledge and attitudes of dentists, physicians, pharmacists, and the general public regarding ingredients in oral hygiene products, especially fluoride. Additionally, this study aimed to identify which ingredients may exhibit potential toxicity based on historical records of any adverse effects being induced by a material/component. Methods: A self-administered questionnaire was used in an online cross-sectional observational study to collect data on sociodemographic characteristics, knowledge of fluoride in dental medicine, fluoride usage practices in oral hygiene products, opinions on ingredient toxicity in oral hygiene products, and personal experiences of adverse reactions to products and their components. The collected data underwent descriptive and regression analyses to reveal patterns and relationships within the dataset. Results: The study found a moderate overall knowledge level regarding fluoride usage in dentistry among participants (Md = 5.00, IQR 2.50–7.00). Healthcare professionals exhibited significantly higher knowledge scores compared to the general population (p ≤ 0.001), with dental professionals displaying the highest scores. Regarding concerns about the usage of fluoride, the majority of respondents (77.0%) did not express any concerns. Minor concerns included the risk of ingestion (6.0%) and dental fluorosis (4.6%). Among the other ingredients in oral hygiene products, respondents named alcohol as the most toxic ingredient (70.3%), followed by artificial colors (53.1%), artificial sweeteners (50.4%), and parabens (50.1%). It is noteworthy that the majority of participants (61.6%) stated that they had never experienced any side effects associated with the use of oral hygiene products. Conclusion: This study underscores disparities in fluoride knowledge between healthcare professionals and the general population in Croatia, with dental experts exhibiting a superior understanding. Despite lingering misconceptions about fluoride content and potential toxicity, the majority of participants acknowledge its oral health benefits and use fluoride products regularly.